2016
DOI: 10.1002/2015jc011405
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of a tracer in the deep Gulf of Mexico

Abstract: A 25 km streak of CF3SF5 was released on an isopycnal surface approximately 1100 m deep, and 150 m above the bottom, along the continental slope of the northern Gulf of Mexico, to study stirring and mixing of a passive tracer. The location and depth of the release were near those of the deep hydrocarbon plume resulting from the 2010 Deepwater Horizon oil well rupture. The tracer was sampled between 5 and 12 days after release, and again 4 and 12 months after release. The tracer moved along the slope at first b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 80 publications
(96 reference statements)
7
53
0
Order By: Relevance
“…They are however significantly larger than Ledwell et al, (2008)'s estimates in Sargasso sea mode water eddies (20 m 2 /s). Although extensive field work and numerical experiments have recently provided important information on the dispersion of tracers in the deep GoM (Ledwell et al, 2016), to the best of our knowledge, no estimate of lateral diffusivity is available for LCRs so that a strict comparison of our results with previous work is not possible. It is, however, important to note that the coarse resolution of the 10.1029/2019GL085600 altimetry data might lead to an overestimate of K h : the radial LHC gradient, which controls the denominator of equation (13), is considerably smoothed on the altimetry grid.…”
Section: 1029/2019gl085600mentioning
confidence: 98%
“…They are however significantly larger than Ledwell et al, (2008)'s estimates in Sargasso sea mode water eddies (20 m 2 /s). Although extensive field work and numerical experiments have recently provided important information on the dispersion of tracers in the deep GoM (Ledwell et al, 2016), to the best of our knowledge, no estimate of lateral diffusivity is available for LCRs so that a strict comparison of our results with previous work is not possible. It is, however, important to note that the coarse resolution of the 10.1029/2019GL085600 altimetry data might lead to an overestimate of K h : the radial LHC gradient, which controls the denominator of equation (13), is considerably smoothed on the altimetry grid.…”
Section: 1029/2019gl085600mentioning
confidence: 98%
“…Although a considerable amount of research has been carried out on the large‐scale flow of water masses within the Gulf of Mexico, relatively little effort has focused on small‐scale mixing processes. Ledwell et al () carried out a tracer‐release experiment at a depth of ∼1,100 m in order to investigate spreading and dissipation of hydrocarbon fluid following an accidental spillage. They estimate a diapycnal diffusivity of order 104 m 2 s −1 across the continental slope of the northern Gulf of Mexico.…”
Section: Introductionmentioning
confidence: 99%
“…This flux is generally considered proportional to the nitrate vertical gradient (S N ) through the relationship F N = K z · S N (with K z the diffusion coefficient; Okubo, 1971). The latest estimate of K z for the interior GOM is 0.15 × 10 −4 m 2 s −1 (Ledwell et al, 2016), which is similar to what is observed in the open ocean (e.g., Ledwell et al, 1998). Thus, considering K z constant, a steeper nitracline in CG (p<0.05, Fig.…”
Section: Nutrient Vertical Distribution In Cyclones and Anticyclonesmentioning
confidence: 99%